Prevalence of cataract and its associated factors among adult diabetic patients attending at diabetic care clinics in Northwest Ethiopia, 2023 - Abebech Fikade Shumye; Melkamu Temeselew Tegegn; Matiyas Mamo Bekele (BMC Public Health)
Abstract Baground Cataract is a major public health concern and the leading cause of blindness and low vision in Ethiopia. However, no studies have been conducted to assess the prevalence of cataract and associated factors among adult diabetic patients in the study area. Therefore, this study aimed to assess the prevalence of cataract and associated factors among adult diabetic patients in Northwest Ethiopia. Methods A multicenter cross-sectional study was conducted in Northwest Ethiopia from May 8 to June 8, 2023. A systematic random sampling technique was used to select study subjects. Data were collected through an in-person interview and physical examination. The data were imported to Kobo Toolbox version 2022 4.4 and exported to Stata version 14. A binary logistic regression was carried out to identify factors associated with cataract, and the strength of association was determined by adjusted odds ratio. A variable with a P-value of < 0.05 at a 95% confidence interval was considered a significant factor for cataract. Results The study included 1100 study subjects with a median age of 52 years. The prevalence of cataract was 42.2% (95%CI: 39.1-45.1%). Older age (AOR = 9.73, 95% CI: 5.53–17.13), ≥ 10 years duration of diabetic mellitus (AOR = 2.77, 95% CI: 1.96–3.90), poor glycemic control (AOR = 1.96, 95% CI: 1.40–2.74), and proliferative diabetic retinopathy (AOR = 4.14, 95% CI: 2.04–8.40), were factors significantly associated with cataract. Conclusions This study revealed a high prevalence of cataract among adult diabetic patients. Older age, longer duration of diabetes mellitus, poor glycemic control, diabetic retinopathy, and proliferative diabetic retinopathy had statistically significant associations with cataract. Therefore better controlling blood sugar levels will reduce the development of cataract. Regular screening of their eye will be also recommended to reduce visual impairment and blindness due cataract.